From Hableány to Maccabi Games- or an eventful summer of the Counter Terrorism Centre: Interview with János Hajdu (Academic Journal of Internal Affairs, 2019)
Probably there is nobody who has not heard about the accident of the river trip boat Hableány last May. Practically parallel to that – in the evening of the following day – the Minister for Interior entitled the leader of the Counter Terrorism Centre to control and coordinate rescue operations. This rescue lasting thirteen days meant a very complicated and for the Centre an unusual task considering that this kind of rescue actions are not part of assignment and scope of the Counter Terrorism Centre. But what does it all mean in the practice, about that talked to János Hajdu, police major general and director-general of the Counter Terrorism Centre, Dr. Zsuzsanna Hornyik.
Keywords: Hableány; accident; Counter Terrorism Centre